An evolutionary game analysis of new energy vehicles promotion considering carbon tax in post-subsidy era. (1st February 2023) - Liao, Dongsheng; Tan, Binbin
Abstract: This paper uses evolutionary game theory to explore an effective carbon taxation mechanism in post-subsidy era based on hoteling demand. First, an evolutionary game model is constructed to explore interplays between local governments and auto-manufacturers. Then, optimal carbon tax mechanism and parameters sensitivity are analyzed and compared in different scenarios using empirical analysis. We conclude that: (1)In subsidy phase-out scenario, static carbon tax policy is better than phasing in carbon tax policy; in subsidy withdrawn scenario, phasing in carbon tax policy can popularize NEVs in a more stable way. (2)Under the mechanism of withdrawal subsidy and carbon tax phase-in, there exist marginal diminishing effects in phase-in rate r and carbon tax rate Tc ; under the mechanism of subsidy phase-out and static carbon tax, both marginal increasing effect and marginal decreasing effect are existed in carbon tax rate Tc . (3)Under the mechanism of withdrawal subsidy and carbon tax phase-in, a threshold effect is found in carbon emission trading revenue Rc, license priority for NEVs consumers η, charging pile coverage rate β, corporate income tax concession Rd, consumers' low carbon preference θ and vehicle purchase tax Tb, while there is a marginal incremental effect in them under the mechanism of withdrawal subsidy and carbon tax phase-in, and the parameters in former mechanism are more sensitive. Further, those parameters are divided into three levels according to their influential degree, in which consumers' low carbon preference θ is at first level. Accordingly, it is suggested that governments implement appropriate carbon tax policies at different industrial developmental phase, supplemented by support policies paying most attention on vigorously promoting low-carbon consumption or subsidizing low-carbon behaviors. Highlights: This paper studies the effect of carbon tax policy on the diffusion of new energy vehicles. This paper finds that the phasing in carbon tax policy is inductive to new energy vehicles' promotion. This paper enriches the research on the influencing factors of new energy vehicles' promotion. This paper provides governments with new policy consideration in post-subsidy era in China. This paper provides new insights on the incentive of carbon tax policy's implementation.